Donald Trump’s anti-Iranian Strategy - A. I. Shumilin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
Against  the  background  of the coupling of a number  of crisis in the Middle East and the Persian Gulf (Syria, Yemen, Iran) the Donald Trump  administration is elaborating its basic strategy toward those conflicts and toward the region as a whole. The centerpiece of the strategy is the task to counter Iran, foremost its nuclear program. From now on the American approaches to other regional crises are determined by this Anti-Iranian logic. It might mean in particular that the developments in Syria are being perceived in Washington primarily in context of the growing US confrontation with Iran. And only in the second turn – in context of seeking solution in Syria and for Syria itself.The New American  strategy toward Iran came across open misunderstanding on the side of the Washington’s partners in Europe who launched a campaign with the aim to resist the Trump’s line as well as to keep on the world community’s deal with Iran concluded in  the year 2015 (JCPOA) which bears on restricting the size of the Iranian  nuclear program versus gradual lifting of international  sanctions from Iran. With intent to minimize  the damage from Trump’s withdrawal from the deal for the European companies in Iran the EU applied two defensive tools in the financial domain  – The Blocking Statute  and  The Special Purpose Vehicle pertaining to secure the financial transactions with  Tehran. Such a clear EU’s withstanding with the USA can hardly prove effective taking into account that the Washington’s stake on countering Iran seems to let Trump’s team to achieve many of the declared objectives in the Middle East. Among them – to mobilize the Sunni community  in the region, to make it get closer to Israel and finally to reestablish the military dominance in the Persian Gulf with ability to control the oil export’s roots there.